1998
DOI: 10.3171/jns.1998.88.6.1075
|View full text |Cite
|
Sign up to set email alerts
|

Antivasospastic and brain-protective effects of a hydroxyl radical scavenger (AVS) after experimental subarachnoid hemorrhage

Abstract: These results demonstrate useful antivasospastic and brain-protective actions of AVS after induction of experimental SAH and provide support for observations of beneficial effects of AVS made in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The importance of antioxidant treatment in preventing neuronal damage has recently been emphasized (23,(59)(60)(61). Vitamin E (62) and a novel free radical scavenger (59) protect against changes in membrane permeability caused by peroxidation and attenuate ischemic and postischemic brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of antioxidant treatment in preventing neuronal damage has recently been emphasized (23,(59)(60)(61). Vitamin E (62) and a novel free radical scavenger (59) protect against changes in membrane permeability caused by peroxidation and attenuate ischemic and postischemic brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin oxidation products (BOXes) may have a similar time course to onset of vasospasm, and they are vasoactive both in vivo and in vitro (Clark et al, 2002). Evidence that oxidative stress may contribute to vasospasm (cerebral and coronary) has been published (Gaetani et al, 1998;Kahler et al, 2001;Matz et al, 1996;Polidori et al, 1997;Reeder et al, 2002); however, antioxidant therapy alone has not proven clinically effective, and is not standard of care (Asano et al, 1984;Asano et al, 1996;Germano et al, 1998;Luo et al, 1995). Thus, oxidative stress alone may not be the sole cause of vasospasm.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the basis of the aforementioned ROS cascadepromoting reactions, a variety of antioxidants such as SOD, 9 the ⅐OH scavenger AVS [(ϩ/Ϫ)-N, NЈ-propylenedinicotinamide], 11,13 ebselen (an agent exhibiting glutathione peroxidase-like activity), 12,14 the antioxidant aminosteroid, 7,8 the singlet oxygen scavenger histidine, 10 and iron chelators [15][16][17] have been shown to be prophylactic against cerebral vasospasm in animal models as well as in SAH patients. Of particular interest is the Fe 2ϩ chelator 2,2Ј-dipyridyl, which has been shown to completely prevent delayed vasospasm in a primate model of SAH, 17 pointing to an important role of the Fe 2ϩ iron ion in the pathogenesis of cerebral vasospasm, as ROS formation requires the ferrous moiety and Fe 2ϩ is a potent trapping agent for NO.…”
Section: Possible Origin Of ⅐Omentioning
confidence: 99%
“…5,6 In support of the theory that ROS are primary pathogens for SAH, a variety of antioxidants have been shown to attenuate cerebral vasospasm in animals and humans. [7][8][9][10][11][12][13][14] We have shown that intracisternal overproduction of ⅐O 2 Ϫ may initiate and/or mediate cerebral arterial vasoconstriction and subsequent structural damage. 3 Moreover, administration of ferrous (Fe 2ϩ ) or ferric (Fe 3ϩ ) iron chelators was shown to mitigate against cerebral vasospasm, providing evidence that the iron-catalyzed Haber-Weiss and Fenton reactions are involved in the mechanism of ROS generation leading to the occurrence of cerebral vasospasm.…”
mentioning
confidence: 99%